Assessment of management commitment in Malaysian public sector - Razana Juhaida Johari; Md. Mahmudul Alam; Jamaliah Said (Cogent Business & Management, 2018)
Currently, the public sector is a matter of global concern due to the constant cases of failures in governance, fraud, inefficacy, and corruption. Management commitment is a critical issue as lack of it could lead to failures in governance, fraud, inefficacy, corruption, as well as weak financial management, particularly in the public sector. This study evaluated the state of present practices of management commitment among public-sector employees in Malaysia. Primary data were collected using a questionnaire survey from 194 heads of departments in the Malaysian federal ministries. The collection of data was in accordance with the perspective of 10 factors in management commitment practices, using a 5-point Likert scale. Factor analysis and descriptive statistics were utilized for data analysis. In addition, data reliability was checked by Cronbach's alpha test, data normality was examined by skewness and kurtosis tests, and data validity was tested by using Kaiser–Meyer Olkin test and Barlett's test. The findings show that 97% of the participants reported that they practised management commitment within their departments. Nevertheless, the priority for these management commitment factors varied according to the service schemes. In general, management commitment practice was the highest within the groups that used the finance scheme and the lowest among the employees who were under the accounting and audit schemes. The result of the study will help policy makers to take the necessary steps to improve the practices of management commitment in the public sector in order to create a more dependable and efficient public sector in Malaysia.
Keywords: 650